Task-Irrelevant Blindsight and the Impact of Invisible Stimuli - Stoerig, Petra (Frontiers in Psychology, 2011)
Despite their subjective invisibility, stimuli presented within regions of absolute cortical blindness can both guide forced-choice behaviour when they are task-relevant and modulate responses to visible targets when they are task-irrelevant. We here tested three hemianopic patients to learn whether their performance in an attention-demanding rapid serial visual presentation task would be affected by task-irrelevant stimuli. Per trial, nine black letters and one white target-letter appeared briefly at fixation; the white letter was to be named at the end of each trial. On 50% of trials, a task-irrelevant disk (-.6 log contrast) was presented to the blind field; in separate blocks, the same or a very low negative contrast distractor was presented to the sighted field. Mean error rates were high and independent of distractor condition, although the high contrast sighted-field disk impaired performance significantly in one participant. However, when trials with and without distractors were considered separately, performance was most impaired by the high contrast disk in the blind field, whereas the same disk in the sighted field had no effect. As this disk was least visible in the blind and most visible in the sighted field, attentional suppression was inversely related to visibility. We suggest that visual awareness, or the processes that generate it and are compromised in the blind hemisphere, enhances or enables effective attentional suppression.